SCREENING OF INDIAN PEANUT GENOTYPES FOR RESISTANCE TO CERCOSPORA LEAFSPOT UNDER SAVANNA CONDITIONS - Méndez‑Natera, Jesús Rafael; Luna‑Tineo, Joseba Andoni; Barrios‑Azócar, Luis Arnaldo; Cedeño, Jesús Rafael (Emirates Journal of Food and Agriculture)
The objective was to evaluate the Indian and Venezuelan peanut cultivars (PC) for agronomic performance and resistance to Cercospora leaf‑spot (CLS) diseases for selection. The study covered three experiments: In the first one, 15 PC were evaluated (13 from India classified as resistant to CL and two native, Desconocida‑36 and Americano Chico (AC)) in a RBD. In the second one, 15 PC (12 from India classified as early maturing) and three native (Rojo, Rosado and AC) in a RBD. In the third experiment, 25 PC were evaluated (22 from India classified as confectionery) and three native (Rojo, Rosado and AC) in a triple lattice design. In all experiments, three replications were used and probability level was 5%. Fungicide aspersions were not carried out. The two species of Cercospora identified were Cercospora arachidicola and Cercosporidium personatum. Peanut cultivars found to be high yielding were Desconocida‑36 with 1944.6 kg/ha and cv. 86325 with 2035.3 kg/ha, both with intermediate tolerance. Cultivars 88401 and 88395 were classified as tolerant because of restricting fungicide application in the experiments.